A financeirização da educação superior: os defeitos do FIES para o desenvolvimento da Kroton Educacional - Nascimento, Emanuelle Lourenço do (2021)
The thesis aims to analyze the effects of the Student Financing Fund (Fies) on the development of Kroton Educacional within the framework of the phenomenon of university education financialization. As a phenomenon that characterized capitalism since the 1970s, financialization expresses growing valorization and autonomization of financial wealth in relation to productive wealth. Since 2007, financialization has been promoting the entrance of Higher Education Institutions (HEIs) in the Brazilian Stock Exchange ( the B3 - Brasil, Bolsa, Balcão), resources contribution through private equity funds, and the realization of mergers and acquisitions in the sector, providing the formation of oligopolies. These publicly traded educational groups also dispute the public funds for education through lobbies, the Brazilian Association for the Development of Higher Education (ABRAES), and the Forum of Entities Representing Private Higher Education (FERESP), which interfere in the regulation of programs like Fies. In the context of the expansion of Fies between 2010 and 2014, publicly traded educational groups showed growth in net revenue, enrollments, and share price on B3. The methodological approach in this research considers historicaldialectical materialism, and its procedures have bibliographic and documental nature. The empirical data was collected in documents from Kroton Educacional and Cogna Educação, the Educational Data Laboratory (LDE), the Higher Education Census (INEP, 2020), the Federal Audit Court - TCU (2016), Hoper Educação (2020), CM Consultoria (2015), the TrandingView platform (2021), the Ministry of Education (2012; 2013; 2014; 2015; 2016; 2017), and the National Fund for Education Development - FNDE (2020) on Fies. The research results show that the regulation of Fies from 2010 to 2014 primarily benefited Kroton Educacional, which is since 2019 a subsidiary of the holding company Cogna Educação, the primary educational oligopoly in Brazil. The decrease in the number of funding granted by Fies since 2015 reshaped the structure and activities developed by the company. Nevertheless, the indiscriminate granting of Fies loans has aided the development of Kroton Educacional, with implications for the private educational sector, especially for higher education institutions.